Mycoplasma genitalium infections: current treatment options and resistance issues - Sethi, Sunil (Infect Drug Resist, 2017)
Mycoplasma genitalium is one of the important causes of non-gonococcal urethritis. Rising incidence and emerging antimicrobial resistance are a major concern these days. The poor clinical outcomes with doxycycline therapy led to the use of azithromycin as the primary drug of choice. Single-dose azithromycin regimen over a period of time was changed to extended regimen following studies showing better clinical cures and less risk of resistance development. However, emerging macrolide resistance, either due to transmission of resistance or drug pressure has further worsened the management of this infection. The issues of drug resistance and treatment failures also exist in cases of M. genitalium infection. At present, the emergence of multidrug-resistant (MDR) M. genitalium strains is an alarming sign for its treatment and the associated public health impact due to its complications. However, newer drugs like pristinamycin, solithromycin, sitafloxacin, and others have shown a hope for the clinical cure, but need further clinical trials to optimize the therapeutic dosing schedules and formulate appropriate treatment regimens. Rampant and inappropriate use of these newer drugs will further sabotage future attempts to manage MDR strains. There is currently a need to formulate diagnostic algorithms and etiology-based treatment regimens rather than the syndromic approach, preferably using combination therapy instead of a monotherapy. Awareness about the current guidelines and recommended treatment regimens among clinicians and local practitioners is of utmost importance. Antimicrobial resistance testing and global surveillance are required to assess the efficacy of current treatment regimens and for guiding future research for the early detection and management of MDR M. genitalium infections.